2004
DOI: 10.1021/ja049605b
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry and Optical Absorbance and Luminescence of Molecule-like Au38 Nanoparticles

Abstract: This paper describes electrochemical and spectroscopic properties of a well-characterized, synthetically accessible, 1.1 nm diam Au nanoparticle, Au(38)(PhC(2)S)(24), where PhC(2)S is phenylethylthiolate. Properties of other Au(38) nanoparticles made by exchanging the monolayer ligands with different thiolate ligands are also described. Voltammetry of the Au(38) nanoparticles in CH(2)Cl(2) reveals a 1.62 V energy gap between the first one-electron oxidation and the first reduction. Based on a charging energy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

64
561
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 458 publications
(626 citation statements)
references
References 50 publications
64
561
1
Order By: Relevance
“…In 1998, Wilcoxon et al reported blue emission at 440 nm from small gold nanoparticles (diameter < 2.5 nm) (67), however, due to the heterogeneity of the solution, the exact size of emissive species was undetermined. Near IR emission was also reported from glutathione encapsulated Au 28 clusters (9) and from tiopronin-capped ~1-nm Au species (68)(69)(70)(71)(72)(73)(74)(75), both in aqueous solution. Compared to well-studied alkali clusters (24,25), the size-dependent electronic structure of these noble metals remained poorly understood, yet a framework (9,23,76) for linking nanoparticle and cluster optical properties through free electron scalings was in place.…”
Section: Fluorescent Gold Nanoclustersmentioning
confidence: 89%
“…In 1998, Wilcoxon et al reported blue emission at 440 nm from small gold nanoparticles (diameter < 2.5 nm) (67), however, due to the heterogeneity of the solution, the exact size of emissive species was undetermined. Near IR emission was also reported from glutathione encapsulated Au 28 clusters (9) and from tiopronin-capped ~1-nm Au species (68)(69)(70)(71)(72)(73)(74)(75), both in aqueous solution. Compared to well-studied alkali clusters (24,25), the size-dependent electronic structure of these noble metals remained poorly understood, yet a framework (9,23,76) for linking nanoparticle and cluster optical properties through free electron scalings was in place.…”
Section: Fluorescent Gold Nanoclustersmentioning
confidence: 89%
“…They have attracted intense research interests recently due to their unique electronic, optical and catalytic properties (33)(34)(35). They are composed of very few Au atoms in the center core with the size less than 1 nm, and as a result they show "molecule-like" optical transitions in the absorption and emission spectra (36). The small-sized thiolate protected Au nanoclusters exhibit exceptional stability and size dependent HOMO-LUMO gap.…”
Section: Introductionmentioning
confidence: 99%
“…[180][181][182] The onset of this IR emission is consistently appearing around 1100 nm, which suggests that visible and IR luminescence are caused by different photophysical mechanisms. As discussed earlier (section 5.2 of this chapter), IR emission is attributed to intraband rather than interband transitions.…”
Section: 181182mentioning
confidence: 94%
“…[179][180][181][182][183] The localized surface plasmons near rough metal nanostructures are presumed to perform a mediating role in the IR emission, 184,185 because these strongly confined fields possess resonances of electrons in the metal, and the associated field gradients give rise to higher-order multipolar transitions. 179 Independently, Varnavski et al also speculated upon a possible role of surface plasmons in intraband excitations.…”
Section: 184mentioning
confidence: 99%
See 1 more Smart Citation